Enhanced mineral powder-based polymer and preparation method thereof

By using mineral powder, silica fume, calcium carbide slag, desulfurization gypsum and other materials, and preparing excitation accelerators, the problems of low early strength of fly ash and high cost of water glass are solved, and the early strength and durability of mineral powder-based polymers are achieved. The performance is improved and the construction performance is improved.

CN119019104BActive Publication Date: 2025-01-21SHIJIAZHUANG TIEDAO UNIV +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507044.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

In the prior art, fly ash has a low early strength, which limits its use in applications that need to quickly meet the strength requirements. At the same time, the cost of water glass as an exciter is high, and excessive calcium-containing substances may lead to a shortening of the settling time but the strength. decline.

Method used

The use of mineral powder as the main active substance, add a small amount of silicon ash and stone residue, desulfurization gypsum as an inspirator, add coarse aggregate and fine material as the skeleton material, and prepare the promotion agent to not add a strong alkali stimulus agent. Below, improve the early intensity and durability of the venom base.

Benefits of technology

It is possible to improve the early strength and durability of mineral powder-based polymers, improve construction performance, and reduce production costs without using strong alkali activators.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of geopolymer building materials, and in particular to an enhanced mineral powder-based geopolymer and a preparation method thereof. The mineral powder is used as a main active substance, a small amount of silica fume is added for activity supplementation, carbide slag and desulfurized gypsum are used as activators, coarse aggregate and fine aggregate are added as skeleton materials, a water reducer is added to improve the fluidity of the slurry, the water consumption of the concrete is reduced, and an activation promoter compatible with the cementitious material is prepared. The early strength and durability of the mineral powder-based geopolymer can be improved without adding a strong alkali activator, and the construction performance can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geopolymer building materials, in particular to a reinforced mineral powder-based polymer and a preparation method thereof. Background Art

[0002] Geopolymer is a new type of inorganic gelling material, mainly composed of [SiO4] 4- Tetrahedron and [AlO4] 6- A three-dimensional network structure formed by tetrahedron polymerization.

[0003] This material has the characteristics of high strength, high hardness, high resistance to chemical corrosion, high fire resistance and the ability to solidify heavy metal ions, and has broad application prospects in the building materials industry.

[0004] The preparation of geopolymers usually involves the formation of inorganic gel materials on a silica-alumina substrate (such as fly ash, coal gangue, kaolin, etc.) under the stimulation of a strong alkaline solution.

[0005] Activator is an additive that can improve the performance of concrete.

[0006] These activators can improve key performance indicators of concrete such as strength, durability and workability, thereby fully enhancing the performance of concrete.

[0007] Activators can promote various reactions in the molding process by changing the chemical composition of the material.

[0008] This can effectively improve the physical and mechanical properties of concrete and make it more durable and reliable in use.

[0009] For example, alkali activators, the use of kaolin and highly active mineral admixtures can prepare high-performance concrete and improve the strength and durability of concrete.

[0010] Reference 1 (Zhao Yanxu, Xiang Junran, Lü Qingfeng, Shan Xiaokang, Chen Yi. Effect of alkali activator on engineering properties of geopolymer-stabilized loess [J]. Journal of Beijing University of Technology, 2021, 47(6): 636-643.) published the use of water glass with different modulus and Baume degrees as an activator to solidify fly ash and loess. Its effect on the engineering properties of solidified loess was studied through compaction test, unconfined compressive strength test, direct shear test, disintegration test and water absorption test. Its effect on the microstructure of solidified loess was studied through scanning electron microscope (SEM) and fully automated surface area and pore size analyzer (Brunner-emmt-teller measurement, BET) test and related analysis was carried out.

[0011] Reference 2 (Song Yue, Lin Na, Ma Yanwei, Yang Lei, Shen Xingmei, Zheng Cuihong, Tan Jie. Effect of composite activator on the performance of steel slag-slag based cementitious materials [J]. Journal of Anhui University of Technology (Natural Science Edition), 2019, 36(1): 24-28.) published an analysis of the appearance, compressive strength and hydration products of steel slag-slag based cementitious materials, and studied the effect of the composite activator of calcium hydroxide and activator D on the stability and compressive strength of steel slag-slag based cementitious materials.

[0012] The results show that: compared with no activator added, the composite activator can significantly stimulate the activity of steel slag-slag based cementitious materials and improve their stability; the order of influencing factors of the compressive strength of cementitious materials is activator D, calcium hydroxide, and steel slag powder; when the mass fractions of steel slag powder, slag powder, calcium hydroxide, and activator D are 40%, 53%, 3%, and 4% respectively, the volume stability of the prepared cementitious material sample is qualified, and the compressive strength is the largest, reaching 15.46MPa.

[0013] The shortcomings of the above technology are:

[0014] (1) Literature 1 gradually uses environmentally friendly recycled materials such as fiber materials and geopolymers as soil solidifiers based on traditional inorganic solidifiers.

[0015] Geopolymer is produced by activating silicoaluminate raw materials with alkaline activators (alkali-aluminosilicate reaction). It has the characteristics of low CO2 emissions and excellent performance. It is a green cementitious material.

[0016] Fly ash, as a raw material of geopolymer, has SiO2, Al2O3 and CaO as its main components, but its glassy shell is stable and not easy to hydrate. Water glass, as an alkaline activator, can destroy the Al-O and Si-O bonds in the glassy structure of fly ash, thus releasing the potential activity of fly ash.

[0017] As a mineral geopolymer, water glass alkali activated fly ash base polymer can effectively utilize industrial solid waste. Many scholars at home and abroad have conducted extensive research on its application in the engineering field.

[0018] However, fly ash has low early strength, which may limit its use in certain applications that require rapid strength development.

[0019] Moreover, the cost of water glass in applications such as as a hydrogen peroxide stabilizer or for paving "glass roads" is relatively high.

[0020] For example, in 1918, the "glass road" built by Swiss engineers had excellent properties, such as being strong and not easy to get dirty, but its high cost limited its wider application.

[0021] (2) Reference 2 found that, in addition to calcium carbonate, calcium-containing substances generally have a strong accelerating effect, which may lead to a significant shortening of the setting time.

[0022] For example, calcium chloride, due to its solubility, can provide a non-uniform nucleation matrix and generate a low calcium-silicon ratio hydrated calcium silicate gel. A small amount of calcium chloride can significantly shorten the setting time of the sample, but its strengthening effect is mainly reflected in the early stage, and excessive calcium-containing substances may cause a decrease in strength due to rapid setting of the sample.

[0023] Although composite activators can significantly improve the activity and stability of cementitious materials, attention must be paid to the type and dosage of the activators.

[0024] For example, if the amount of activator added is too high, it may lead to reduced material properties, such as reduced strength or poor durability.

[0025] In addition, some activators may react adversely with other components in the cementitious material, affecting the performance of the final product.

[0026] In practical applications, too fast setting time may cause inconvenience to construction operations, especially in large projects that require longer working time.

[0027] Therefore, it is necessary to reasonably control the dosage of the activator to adjust the setting time. Summary of the invention

[0028] In order to solve the problems existing in the prior art, the present invention provides an enhanced mineral powder-based polymer, which uses mineral powder as the main active substance, adds a small amount of silica fume for activity supplement, uses calcium carbide slag and desulfurized gypsum as activators, adds coarse aggregate and fine aggregate as skeleton materials, adds a water reducer to improve the fluidity of the slurry, reduces the water consumption of concrete, and prepares an activation promoter compatible with the cementitious material. The early strength and durability of the mineral powder-based polymer can be improved without adding a strong alkali activator, and the construction performance can be improved.

[0029] Specifically, the enhanced mineral powder-based polymer of the present invention is composed of the following raw materials in parts by weight: 400-450 parts of mineral powder, 10-15 parts of silica fume, 20-30 parts of carbide slag, 10-20 parts of desulfurized gypsum, 950-1000 parts of coarse aggregate, 700-800 parts of fine aggregate, 8-10 parts of water reducer, 4-6 parts of excitation promoter, and 190-200 parts of water.

[0030] The main active substance of the mineral powder is active silicon dioxide, and it also contains some active aluminum oxide and calcium oxide. The present invention adopts the mineral powder as the main active raw material, but it needs a strong alkali to excite the material to achieve higher mechanical properties. In order to reduce the use of strong alkali, the present invention adopts carbide slag and desulfurized gypsum as alkaline and sulfate activators. In order to compensate for the strength development of the mineral powder at low alkaline activators, a small amount of silica ash is supplemented as a high-activity silicon source, and an excitation promoter is prepared to accelerate the hydration process of the cementitious material.

[0031] Preferably, the preparation process of the excitation accelerator is:

[0032] a. Weigh each raw material by mass,

[0033] b. Add 2 parts of phosphite and 35-40 parts of deionized water into the reactor, heat up, stir,

[0034] c. Add 1-2 parts of alkylamine oxide and 0.5-1 parts of N-alkylpyrrolidone to the reaction kettle and stir.

[0035] d. Continue to add 6-10 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly.

[0036] e. Add 35-45 parts of ethyl acetate and 8-10 parts of saturated lime water into the reaction kettle and stir to obtain the product.

[0037] In the present invention, in a liquid phase environment, γ-chloropropylmethyldiethoxysilane reacts with ethyl acetate to form a chemical bond, and a stable reaction environment is formed by phosphite, saturated lime water, alkylamine oxide and N-alkylpyrrolidone. The formed ester excitation promoter can promote the hydration of mineral powder and silica fume in an alkaline environment. The organic component in the excitation promoter promotes the dissociation and dissolution of active groups and metal ions, thereby increasing the concentration of reactants in the liquid phase. The excitation promoter is also alkaline and can provide a portion of Ca 2+ It is suitable for the preparation of geopolymers with high mineral powder and low silica fume as active materials in a low-alkali environment.

[0038] Preferably, the mineral powder is at least one of S95 grade mineral powder and S105 grade mineral powder.

[0039] Preferably, the coarse aggregate is 5-25 mm continuously graded crushed stone.

[0040] Preferably, the fine aggregate is at least one of river sand, quartz sand and machine-made sand, and the fineness modulus is 2.2-2.6.

[0041] Preferably, the water reducer is a polycarboxylic acid water reducer with a water reduction rate of ≥20%.

[0042] Preferably, in the process for preparing the excitation accelerator, the temperature in step b is raised to 55-65° C. and the stirring time is 5-8 min.

[0043] Preferably, in the process for preparing the excitation promoter, the stirring time in step c is 10-13 min.

[0044] Preferably, in the process for preparing the excitation promoter, the rapid stirring speed in step d is 700-800 r / min and the time is 15-18 min.

[0045] Preferably, in the process for preparing the excitation promoter, the stirring time in step e is 25-30 min.

[0046] The present invention also relates to a method for preparing the enhanced mineral powder-based polymer, which specifically comprises the following steps:

[0047] 1) Weigh each raw material by mass.

[0048] 2) Add mineral powder, silica fume, carbide slag and desulfurized gypsum into the mixer, stir, add coarse aggregate and stir evenly.

[0049] 3) Mix the water reducer, activator and water evenly to obtain liquid material.

[0050] 4) Add fine aggregate and liquid material into the mixer and mix evenly to obtain slurry.

[0051] 5) Shape and cure the slurry.

[0052] The present invention has the following technical advantages:

[0053] 1. The present invention uses mineral powder as the main active material, adds silica fume as a supplement, uses carbide slag and desulfurized gypsum as activators, and the cementitious materials are all industrial waste, which is waste-recycling and environmentally friendly.

[0054] 2. The present invention does not require the addition of strong alkaline activators such as sodium hydroxide, and has little impact on the environment and construction personnel.

[0055] 3. The activating accelerator prepared by the present invention can promote the hydration reaction of the mineral powder-based polymer, destroy the surface structure of slag and silica fume, and make Ca 2+ 、Al 3+ 、Si 4+ Active substances such as CSH and CASH are dissolved and repolymerized to form CSH and CASH gels, which can replenish some Ca 2+ , thereby increasing the strength of concrete,

[0056] 4. The reinforced mineral powder-based polymer of the present invention has good mechanical properties, good construction performance and durability.

[0057] 5. The preparation process of the present invention is simple, and the product can be widely used in engineering construction such as buildings, roads, bridges, tunnels, etc. DETAILED DESCRIPTION

[0058] In order to characterize the technical effect of the present invention, geopolymer was prepared and its performance was tested. During the test, the mineral powder used was S95 grade mineral powder, the coarse aggregate used was 5-25mm continuously graded crushed stone, the fine aggregate used was river sand with a fineness modulus of 2.4, and the water reducing agent used was a polycarboxylate water reducing agent with a water reducing rate of 25%.

[0059] Example 1

[0060] Geopolymer is composed of the following raw materials in parts by weight: 420 parts of mineral powder, 12 parts of silica fume, 25 parts of carbide slag, 20 parts of desulfurized gypsum, 980 parts of coarse aggregate, 780 parts of fine aggregate, 8 parts of water reducer, 5 parts of activating accelerator, 195 parts of water,

[0061] The preparation process of the excitation accelerator is as follows:

[0062] a. Weigh each raw material by mass,

[0063] b. Add 2 parts of phosphite and 40 parts of deionized water into the reactor, heat to 60°C, and stir for 7 minutes.

[0064] c. Add 2 parts of alkylamine oxide and 1 part of N-alkylpyrrolidone to the reactor and stir for 12 minutes.

[0065] d. Add 7 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly at 800 r / min for 18 min.

[0066] e. Add 40 parts of ethyl acetate and 9 parts of saturated lime water into the reaction kettle and stir for 28 minutes to obtain the product.

[0067] After testing, the initial expansion of the geopolymer concrete slurry was 650mm, the initial setting time was 8h40min, the final setting time was 12h20min, the 3d compressive strength was 20.2MPa, the 3d flexural strength was 2.1MPa, the 28d compressive strength was 53.4MPa, the 28d flexural strength was 5.6MPa, and there were no cracks on the surface of the specimen.

[0068] Example 2

[0069] Geopolymer is composed of the following raw materials in parts by weight: 440 parts of mineral powder, 15 parts of silica fume, 26 parts of carbide slag, 13 parts of desulfurized gypsum, 980 parts of coarse aggregate, 780 parts of fine aggregate, 9 parts of water reducer, 6 parts of activating accelerator, and 195 parts of water.

[0070] The preparation process of the excitation accelerator is as follows:

[0071] a. Weigh each raw material by mass,

[0072] b. Add 2 parts of phosphite and 38 parts of deionized water into the reactor, heat to 60°C, and stir for 8 minutes.

[0073] c. Add 1 part of alkylamine oxide and 1 part of N-alkylpyrrolidone to the reactor and stir for 12 minutes.

[0074] d. Add 9 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly at 800 r / min for 15 min.

[0075] e. Add 40 parts of ethyl acetate and 8 parts of saturated lime water into the reactor and stir for 30 minutes to obtain the product.

[0076] After testing, the initial expansion of the geopolymer concrete slurry was 670mm, the initial setting time was 7h50min, the final setting time was 11h15min, the 3d compressive strength was 21.5MPa, the 3d flexural strength was 2.2MPa, the 28d compressive strength was 55.6MPa, the 28d flexural strength was 5.8MPa, and there were no cracks on the surface of the specimen.

[0077] Comparative Example 1

[0078] Geopolymer is composed of the following raw materials in parts by weight: 440 parts of mineral powder, 25 parts of carbide slag, 20 parts of desulfurized gypsum, 980 parts of coarse aggregate, 780 parts of fine aggregate, 8 parts of water reducer, 5 parts of activating accelerator, 195 parts of water,

[0079] The preparation process of the excitation accelerator is as follows:

[0080] a. Weigh each raw material by mass,

[0081] b. Add 2 parts of phosphite and 40 parts of deionized water into the reactor, heat to 60°C, and stir for 7 minutes.

[0082] c. Add 2 parts of alkylamine oxide and 1 part of N-alkylpyrrolidone to the reactor and stir for 12 minutes.

[0083] d. Add 7 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly at 800 r / min for 18 min.

[0084] e. Add 40 parts of ethyl acetate and 9 parts of saturated lime water into the reaction kettle and stir for 28 minutes to obtain the product.

[0085] After testing, the initial expansion of the geopolymer concrete slurry was 650mm, the initial setting time was 10h55min, the final setting time was 14h30min, the 3d compressive strength was 17.3MPa, the 3d flexural strength was 1.8MPa, the 28d compressive strength was 49.8MPa, the 28d flexural strength was 4.7MPa, and there were no cracks on the surface of the specimen.

[0086] Comparative Example 2

[0087] The geopolymer is composed of the following raw materials in parts by weight: 420 parts of mineral powder, 12 parts of silica fume, 30 parts of carbide slag, 20 parts of desulfurized gypsum, 980 parts of coarse aggregate, 780 parts of fine aggregate, 8 parts of water reducer and 195 parts of water.

[0088] After testing, the initial expansion of the geopolymer concrete slurry was 520mm, the initial setting time was 18h10min, the final setting time was 24h, the 3d compressive strength was 9.1MPa, the 3d flexural strength was 1.0MPa, the 28d compressive strength was 35.3MPa, the 28d flexural strength was 3.1MPa, and there were microcracks on the surface of the specimen.

[0089] Comparative Example 3

[0090] The geopolymer is composed of the following raw materials in parts by weight: 420 parts of mineral powder, 12 parts of silica fume, 25 parts of carbide slag, 20 parts of water glass, 980 parts of coarse aggregate, 780 parts of fine aggregate, 8 parts of water reducer and 195 parts of water.

[0091] After testing, the initial expansion of the geopolymer concrete slurry was 570mm, the initial setting time was 2h50min, the final setting time was 4h05min, the 3d compressive strength was 19.7MPa, the 3d flexural strength was 1.9MPa, the 28d compressive strength was 40.6MPa, the 28d flexural strength was 4.3MPa, and the surface of the specimen was cracked.

[0092] Comparative Example 4

[0093] Geopolymer is composed of the following raw materials in parts by weight: 420 parts of mineral powder, 12 parts of silica fume, 25 parts of carbide slag, 20 parts of desulfurized gypsum, 980 parts of coarse aggregate, 780 parts of fine aggregate, 8 parts of water reducer, 5 parts of activating accelerator, 195 parts of water,

[0094] The preparation process of the excitation accelerator is as follows:

[0095] a. Weigh each raw material by mass,

[0096] b. Add 2 parts of phosphite and 40 parts of deionized water into the reactor, heat to 60°C, and stir for 7 minutes.

[0097] c. Add 2 parts of alkylamine oxide and 1 part of N-alkylpyrrolidone to the reactor and stir for 12 minutes.

[0098] d. Add 7 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly at 800 r / min for 18 min.

[0099] e. Add 40 parts of ethyl acetate into the reaction kettle and stir for 28 minutes to obtain.

[0100] After testing, the initial expansion of the geopolymer concrete slurry was 630mm, the initial setting time was 9h10min, the final setting time was 13h40min, the 3d compressive strength was 15.2MPa, the 3d flexural strength was 1.4MPa, the 28d compressive strength was 46.0MPa, the 28d flexural strength was 4.2MPa, and there were no cracks on the surface of the specimen.

[0101] Comparative Example 5

[0102] Geopolymer is composed of the following raw materials in parts by weight: 320 parts of mineral powder, 100 parts of fly ash, 12 parts of silica fume, 25 parts of carbide slag, 20 parts of desulfurized gypsum, 980 parts of coarse aggregate, 780 parts of fine aggregate, 8 parts of water reducer, 5 parts of activating accelerator, and 195 parts of water.

[0103] The preparation process of the excitation accelerator is as follows:

[0104] a. Weigh each raw material by mass,

[0105] b. Add 2 parts of phosphite and 40 parts of deionized water into the reactor, heat to 60°C, and stir for 7 minutes.

[0106] c. Add 3 parts of alkyl amine oxide to the reactor and stir for 12 minutes.

[0107] d. Add 20 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly at 800 r / min for 18 min.

[0108] e. Add 20 parts of ethyl acetate and 9 parts of saturated lime water into the reactor and stir for 28 minutes to obtain the product.

[0109] After testing, the geopolymer concrete slurry was found to be bleeding, the initial setting time was 15h30min, the final setting time was 18h10min, the 3d compressive strength was 12.9MPa, the 3d flexural strength was 1.3MPa, the 28d compressive strength was 40.7MPa, the 28d flexural strength was 4.2MPa, and there were microcracks on the surface of the specimen.

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A reinforced mineral powder-based polymer, characterized in that: It is composed of the following raw materials in parts by weight: 400-450 parts of mineral powder, 10-15 parts of silica fume, 20-30 parts of carbide slag, 10-20 parts of desulfurized gypsum, 950-1000 parts of coarse aggregate, 700-800 parts of fine aggregate, 8-10 parts of water reducer, 4-6 parts of excitation accelerator, 190-200 parts of water, The preparation process of the excitation accelerator is as follows: a. Weigh each raw material by mass, b. Add 2 parts of phosphite and 35-40 parts of deionized water into the reactor, heat up, stir, c. Add 1-2 parts of alkylamine oxide and 0.5-1 parts of N-alkylpyrrolidone to the reaction kettle and stir. d. Continue to add 6-10 parts of γ-chloropropylmethyldiethoxysilane to the reactor and stir rapidly. e. Add 35-45 parts of ethyl acetate and 8-10 parts of saturated lime water into the reaction kettle and stir to obtain the product.

2. The enhanced mineral powder-based polymer according to claim 1, characterized in that: The mineral powder is at least one of S95 grade mineral powder and S105 grade mineral powder.

3. The enhanced mineral powder-based polymer according to claim 1, characterized in that: The coarse aggregate is 5-25 mm continuously graded crushed stone.

4. The enhanced mineral powder-based polymer according to claim 1, characterized in that: The fine aggregate is at least one of river sand, quartz sand and machine-made sand, and has a fineness modulus of 2.2-2.

6.

5. The enhanced mineral powder-based polymer according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥20%.

6. The enhanced mineral powder-based polymer according to claim 1, characterized in that: In the process for preparing the excitation accelerator, the temperature in step b is raised to 55-65° C. and the stirring time is 5-8 min.

7. The enhanced mineral powder-based polymer according to claim 1, characterized in that: In the process for preparing the excitation accelerator, the stirring time in step c is 10-13 minutes.

8. The enhanced mineral powder-based polymer according to claim 1, characterized in that: In the process for preparing the excitation accelerator, the rapid stirring speed in step d is 700-800 r / min and the time is 15-18 min.

9. The enhanced mineral powder-based polymer according to claim 1, characterized in that: In the process for preparing the excitation accelerator, the stirring time in step e is 25-30 minutes.

10. The method for preparing the enhanced mineral powder-based polymer according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by mass. 2) Add mineral powder, silica fume, carbide slag and desulfurized gypsum into the mixer, stir, add coarse aggregate and stir evenly. 3) Mix the water reducer, activator and water evenly to obtain liquid material. 4) Add fine aggregate and liquid material into the mixer and mix evenly to obtain slurry. 5) Shape and cure the slurry.

Citation Information

Patent Citations

  • Inorganic polymer grouting plugging material and production process thereof

    CN112194975A

  • Accelerated excitation method for gelling activity of high-silicon-aluminum copper tailings

    CN115057640A